2018
DOI: 10.3389/fnbeh.2018.00180
|View full text |Cite
|
Sign up to set email alerts
|

Non-motor Behavioral Alterations of PGC-1α-Deficient Mice – A Peculiar Phenotype With Slight Male Preponderance and No Apparent Progression

Abstract: Dysfunction of peroxisome proliferator-activated receptor gamma coactivator-1alpha (PGC-1α) has been linked to various neurodegenerative and neuropsychiatric disorders; however, reports on psychic behavioral alterations on PGC-1α-deficient animals are sparse. The present study revisited prior observations of anxiety-related, depression-related, and hippocampal memory-related observations having been made on different PGC-1α-deficient murine strains, in a large-scale analysis on whole-body full-length (FL-)PGC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…3H), which may be indicative of increased anxiety and impaired swimming-related motor coordination, respectively. Interestingly, conflicting findings have been reported on anxiety-like behaviours for the full body exon 3 deletion alleles (Leone et al, 2005;Szalardy et al, 2018). Finally, we found that female, but not male SINE KO homozygous mutants, had significantly higher target quadrant preferences relative to control animals in the Morris water maze ( Fig.…”
Section: Mutation Of the Sine In Mice Preserves Normal Brain Anatomy supporting
confidence: 45%
See 1 more Smart Citation
“…3H), which may be indicative of increased anxiety and impaired swimming-related motor coordination, respectively. Interestingly, conflicting findings have been reported on anxiety-like behaviours for the full body exon 3 deletion alleles (Leone et al, 2005;Szalardy et al, 2018). Finally, we found that female, but not male SINE KO homozygous mutants, had significantly higher target quadrant preferences relative to control animals in the Morris water maze ( Fig.…”
Section: Mutation Of the Sine In Mice Preserves Normal Brain Anatomy supporting
confidence: 45%
“…Behavioural changes including hyperactivity and severe impaired motor coordination in the rotarod test were associated with the brain lesions found in the exon 3 deletion alleles (Lucas et al, 2012). However, more recent studies found less severe behavioural abnormalities in brainspecific conditional alleles of the exon 3 that were deemed to be unrelated to the neuropathology (Szalardy et al, 2016a;Szalardy et al, 2018). The extent to which the SSR-SINE-exon2 isoform contributes to these phenotypes is unknown.…”
Section: Mutation Of the Sine In Mice Preserves Normal Brain Anatomy mentioning
confidence: 98%
“…Why the SINE KO animals can rapidly overcome the initial swim speed deficits is unclear. Interestingly, conflicting findings have been reported on anxiety-like behaviours for the full body exon 3 deletion alleles that retain an N-terminal truncated transcript (Leone et al, 2005;Szalardy et al, 2018). Finally, we found that female, but not male SINE KO homozygous mutants, had significantly higher target quadrant preferences relative to control animals in the Morris water maze (Fig 2G), suggesting improved spatial learning and memory (Vorhees & Williams, 2014).…”
Section: The Ssr-sine-exon 2 Isoform Of Pgc1α Is Translated Into Proteinmentioning
confidence: 51%
“…This is relevant considering different studies showing that exercise can reduce anxiety (reviewed in Anderson and Shivakumar, 2013). Furthermore, PGC-1α and BDNF levels have also been altered in rodents with anxiety-like behavior (Govindarajan et al, 2006;Szalardy et al, 2018), and both PGC-1α and BDNF can have anxiolytic properties (Agrawal et al, 2014;Xie et al, 2019). Exercise also reduces panic disorder, which is a type of anxiety disorder, through increasing BDNF concentration in serum (Strohle et al, 2010).…”
Section: Fndc5/irisin In Neuropsychiatric Disordersmentioning
confidence: 99%